answersLogoWhite

0


Best Answer

With all due respect, you don't really want to know howto solve it.

You just want the solution.

csc(Θ) = 1/sin(Θ)

tan(Θ) = sin(Θ)/cos(Θ)

csc(Θ) x tan(Θ) = 1/sin(Θ) x sin(Θ)/cos(Θ) = 1/cos(Θ) = sec(Θ)

User Avatar

Wiki User

โˆ™ 2013-02-21 05:32:14
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
846 Reviews

Add your answer:

Earn +20 pts
Q: How do you simplify csc theta tan theta?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you simplify cos theta times csc theta divided by tan theta?

'csc' = 1/sin'tan' = sin/cosSo it must follow that(cos) (csc) / (tan) = (cos) (1/sin)/(sin/cos) = (cos) (1/sin) (cos/sin) = (cos/sin)2


How do you simplify sin theta times csc theta divided by tan theta?

Since sin(theta) = 1/cosec(theta) the first two terms simply camcel out and you are left with 1 divided by tan(theta), which is cot(theta).


How do you get the csc theta given tan theta in quadrant 1?

If tan(theta) = x then sin(theta) = x/(sqrt(x2 + 1) so that csc(theta) = [(sqrt(x2 + 1)]/x = sqrt(1 + 1/x2)


How do you simplify csc theta -cot theta cos theta?

For a start, try converting everything to sines and cosines.


How do i simplify csc theta divided by sec theta?

By converting cosecants and secants to the equivalent sine and cosine functions. For example, csc theta is the same as 1 / sin thetha.


What is csc theta?

That depends on the value of the angle, theta. csc is short for "cosecans", and is the reciprocal of the sine. That is, csc theta = 1 / sin theta.


How do you simplify tan theta cos theta?

Remember that tan = sin/cos. So your expression is sin/cos times cos. That's sin(theta).


What is cos theta multiplied by csc theta?

It is cotangent(theta).


How do you simplify csc theta cot theta cos theta?

cosec(q)*cot(q)*cos(q) = 1/sin(q)*cot(q)*cos(q) = cot2(q)


Csc x tan x?

If you want to simplify that, it usually helps to express all the trigonometric functions in terms of sines and cosines.


If tansqtheta plus 5tantheta0 find the value of tantheta plus cottheta?

tan2(theta) + 5*tan(theta) = 0 => tan(theta)*[tan(theta) + 5] = 0=> tan(theta) = 0 or tan(theta) = -5If tan(theta) = 0 then tan(theta) + cot(theta) is not defined.If tan(theta) = -5 then tan(theta) + cot(theta) = -5 - 1/5 = -5.2


What is tan x csc x?

tan(x)*csc(x) = sec(x)

People also asked